Investigation of the hydrogenation of 5-methylfurfural by noble metal nanoparticles in a microcapillary reactor - Gmeiner, Julia Renate; Leopold, Max; Behrens, Silke; Spliethoff, Bernd; Trapp, Oliver (ChemSusChem, 2016)
Abstract On-column reaction gas chromatography (ocRGC) was successfully utilized as high-throughput platform for monitoring of the conversion and selectivity of hydrogenation of 5-methylfurfural catalyzed by polymer-stabilized Ru and Pd nanoparticles. We were able to elucidate the effect of various reaction conditions, mainly together with the catalyst loading on the conversion rate and the selectivity of the reaction. Our strategy yields significant improvements in reaction analysis times and cost effectiveness in comparison to standard methods. We are able to demonstrate that ocRGC approach provides valuable information about the reaction system that gives scientists a tool to design suitable catalytic systems for enhanced sustainable chemistry in the future.
Gesehen am 23.06.2020